2016
DOI: 10.1377/hlthaff.2015.1170
|View full text |Cite
|
Sign up to set email alerts
|

The Great Recession And Increased Cost Sharing In European Health Systems

Abstract: European health systems are increasingly adopting cost-sharing models, potentially increasing out-of-pocket expenditures for patients who use health care services or buy medications. Government policies that increase patient cost sharing are responding to incremental growth in cost pressures from aging populations and the need to invest in new health technologies, as well as to general constraints on public expenditures resulting from the Great Recession (2007-09). We used data from the Survey of Health, Agein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 25 publications
4
32
0
2
Order By: Relevance
“…Thirdly, our findings are in line with the global priority areas reflected in the Sustainable Development Goals from 2015 [ 88 ]. Considering access to healthcare, it confirms the ultimate importance of financial protection in achieving comprehensive universal health insurance coverage.…”
Section: Discussionsupporting
confidence: 86%
“…Thirdly, our findings are in line with the global priority areas reflected in the Sustainable Development Goals from 2015 [ 88 ]. Considering access to healthcare, it confirms the ultimate importance of financial protection in achieving comprehensive universal health insurance coverage.…”
Section: Discussionsupporting
confidence: 86%
“…Our survey data showed that average OOPE almost doubled between 2010 and 2015, mostly due to greater number of people being required to pay for prescription drugs28 and healthcare services, either as user fees for public services or increasing use of private services to avoid deteriorating conditions in the public healthcare system. Other European countries experienced increases in OOPE, following the recent recession29. The impact of the crisis on healthcare extends beyond access factors and may include declining quality of care, aging infrastructure and staff shortages, which might have important short- and long-term implications for morbidity and mortality, such as adverse events of medical care, which seem to have increased in Greece during the crisis1430.…”
Section: Discussionmentioning
confidence: 99%
“… • Does not examine perceived barriers on access to care. Palladino et al, 2016 [ 2 ] Austria, Belgium, Czech Republic, Denmark, France, Germany, Netherlands, Spain, Sweden, Switzerland Survey of people age 50 and older from Health, Ageing and Retirement in Europe, with data on changes in OOP spending and experiencing catastrophic OOP spending (30% or more of income), from 2006/7 to 2013 (Great Recession) • Very large range in changes in OOP spending (− 11% in Netherlands to + 101% in Austria). • Increase in catastrophic spending: from 2.3 to 3.9% over study period.…”
Section: Introductionmentioning
confidence: 99%